Effect of waste foundry sand and fly ash on mechanical and fresh properties of concrete. (2021) - Reshma, T.V.; Manjunatha, M.; Sankalpasri, S.; Tanu, H.M.
Abstract: This study reports the experimental investigation about the performance of fly ash and untreated waste foundry sand on fresh and hardened state of concrete mix. In this research, 30% fly ash is kept constant as a partial replacement of cement and Natural river sand is replaced with waste foundry sand (WFS) in varying percentages (0%, 10%, 20%, 30% and 40%) for M40 grade concrete. Compaction factor test and slump cone test is conducted to assess the fresh properties of concrete. Similarly, Compressive, split tensile and flexural strength tests are conducted to evaluate the mechanical properties of concrete as per Indian standard. This investigation also covers ultrasonic pulse velocity test to assess the quality of hardened concrete at 7, 14, 28, and 90 days curing period. Based on investigation, test results indicate that use of WFS as a partial replacement of sand in concrete improves the mechanical and fresh properties of concrete up to 30% replacement. Thereafter a marginal decrease in strength is noticed for 40% replacement level. Similarly, the mixes containing 30% WFS exhibits better quality when compared to reference mix having 0% waste foundry sand. As a sustainable approach, use of WFS up to 30% have a greater impact on reducing cost of construction and makes concrete eco-friendly.